UV LEVEL MONITORING IN ANDROID-BASED SKIN HEALTH SYSTEMS - Herlina L, Yeli; Rafsyam, Yenniwarti (Politeknik Negeri Jakarta, 2024)
This research proposes a system to monitor the level of UV exposure to android-based skin, using the VEML6075 sensor and ESP32 module. Excessive UV exposure can have a negative impact on skin health such as premature aging and the risk of skin cancer. In this research, ESP32 module is designed and integrated with VEML6075 sensor to measure UV level accurately and send UV level data to android application through internet connection. The android application created allows users to monitor UV exposure levels in various environmental conditions. In addition, the application provides suggestions and alerts based on UV levels, helping users to take appropriate actions in caring for skin health. Tests were conducted on 3 environmental conditions namely indoors, indoors exposed to sunlight and outdoors exposed to direct sunlight. Also testing was carried out at 09.00 WIB to 15.00 WIB with a distance of 30 minutes. The results of the test obtained UV levels from 0.00125 to 5.02324.